Do Educational Inequalities Exist in Online Learning amidst Covid-19 Pandemic? Experiences of Higher Education Students in West Sulawesi - Bulqia Mas'ud (LP. Ma'arif Janggan Magetan, 2023)
Several studies prove that the visible factors of educational inequalities are socioeconomic status (SES) disparities in society. Students from rural areas and poor families face difficulties accessing high-quality Information and Communication Technology for online learning. The digital divide in urban and rural areas has become more evident during the covid-19 pandemic. The purpose of this study is to investigate whether educational inequalities exist in the online learning experiences of students in West Sulawesi amidst Covid-19 pandemic. Quantitative research was applied in this study using random sampling from 381 students in West Sulawesi. Furthermore, the data were assessed with a one-way ANOVA test. The descriptive statistic of the population reveals that most higher education students in West Sulawesi come from very low to low SES families. The test of difference confirms that students who live in rural, suburban, and urban areas showed a different level of technology access where students from rural areas have lower access to technology for online learning. However, the result evinces no difference in accessing technology for online learning across the socioeconomic status levels. For further investigation, the researcher recommends doing in-depth exploration specifically in the population to find an accurate answer of why educational inequalities do not exist across SES level.